1976
DOI: 10.1148/118.2.367
|View full text |Cite
|
Sign up to set email alerts
|

Persistent Basilar/Middle Meningeal Artery Anastomosis

Abstract: Three cases of a basilar/middle meningeal artery anastomosis are demonstrated angiographically. No reference to previous angiographic demonstration of this vascular anomaly has been found in the literature, and only one similar case with an anatomical description has been located. An embryological explanation of this rare anastomosis is presented.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
43
0

Year Published

1981
1981
2023
2023

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 32 publications
(43 citation statements)
references
References 0 publications
0
43
0
Order By: Relevance
“…of the internal carotid artery via a persistent stapedial artery. 1,5,8 The ipsilateral foramen spinosum was absent radiographically in one of Seeger and H e m m e r ' s cases and in the autopsy study by Altmann. The appearance of the foramina spinosa in the current case was not noted.…”
Section: Discussionmentioning
confidence: 85%
See 1 more Smart Citation
“…of the internal carotid artery via a persistent stapedial artery. 1,5,8 The ipsilateral foramen spinosum was absent radiographically in one of Seeger and H e m m e r ' s cases and in the autopsy study by Altmann. The appearance of the foramina spinosa in the current case was not noted.…”
Section: Discussionmentioning
confidence: 85%
“…, 9,12 The angiographic appearance of unilateral BA-M M A anastomosis has been described in five patients. 3,8,11 The anomalous anastomotic vessel always originated from the basilar artery several millimeters proximal to the SCA. Altmann ~ described an abnormal vessel in a 7-month-old fetus, termed the "acoustico-facial artery," which arose from the basilar artery between the anterior and posterior inferior cerebellar arteries.…”
Section: Discussionmentioning
confidence: 99%
“…Various sources of anomalous origin of the MMA have been reported in the literature (Table 1). 3–12 Some authors have described the anomalous origin of the MMA from the basilar artery 2–6 . The very first case of MMA origin from basilar artery was reported by Altman in 1947 during the postmortem dissection of a 7‐month old fetus 2 .…”
Section: Discussionmentioning
confidence: 99%
“…The very first case of MMA origin from basilar artery was reported by Altman in 1947 during the postmortem dissection of a 7‐month old fetus 2 . After the aforementioned anatomical description, Seeger and Hemmer, in 1976, described 3 patients with the first angiographic evidence of left MMA origin from the basilar artery 3 . Waga et al reported a single case of basilar‐MMA anastomosis in a 47‐year‐old man during angiography.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation